Investigation of the Sharkskin melt instability using optical Fourier analysis. Issue 24 (19th December 2019) - Gansen, Alex; Řehoř, Martin; Sill, Clemens; Polińska, Patrycja; Westermann, Stephan; Dheur, Jean; Hale, Jack S.; Baller, Jörg
ABSTRACT: An optical method allowing the characterization of melt flow instabilities typically occurring during an extrusion process of polymers and polymer compounds is presented. It is based on a camera‐acquired image of the extruded compound with a reference length scale. Application of image processing and transformation of the calibrated image to the frequency domain yields the magnitude spectrum of the instability. The effectiveness of the before mentioned approach is shown on Styrene‐butadiene rubber (SBR) compounds, covering a wide range of silica filler content, extruded through a Göttfert capillary rheometer. The results of the image‐based analysis are compared with the results from the sharkskin option, a series of highly sensitive pressure transducers installed inside the rheometer. A simplified version of the code used to produce the optical analysis results is included as supplementary material. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48806. Abstract : An optical method allowing the characterization of melt instabilities typically occurring during an extrusion process of SBR compounds is presented. It is based on a camera‐acquired image of the extruded compound with a reference length scale. Application of image processing and transformation of the calibrated image to the frequency domain allows the characterization of the instability.